Unique peptidic agonists of a juvenile hormone receptor with species-specific effects on insect development and reproduction - Tumova, Sarka; Milacek, Matej; Šnajdr, Ivan; Muthu, Magesh; Tuma, Roman; Reha, David; Jedlicka, Pavel; Bittova, Lenka; Novotna, Adela; Majer, Pavel; Sedlak, David; Jindra, Marek (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Juvenile hormones (JHs) control insect metamorphosis and reproduction. JHs act through a receptor complex consisting of methoprene-tolerant (Met) and taiman (Tai) proteins to induce transcription of specific genes. Among chemically diverse synthetic JH mimics (juvenoids), some of which serve as insecticides, unique peptidic juvenoids stand out as being highly potent yet exquisitely selective to a specific family of true bugs. Their mode of action is unknown. Here we demonstrate that, like established JH receptor agonists, peptidic juvenoids act upon the JHR Met to halt metamorphosis in larvae of the linden bug, Pyrrhocoris apterus. Peptidic juvenoids induced ligand-dependent dimerization between Met and Tai proteins from P. apterus but, consistent with their selectivity, not from other insects. A cell-based split-luciferase system revealed that the Met-Tai complex assembled within minutes of agonist presence. To explore the potential of juvenoid peptides, we synthesized 120 new derivatives and tested them in Met-Tai interaction assays. While many substituents led to loss of activity, improved derivatives active at sub-nanomolar range outperformed hitherto existing peptidic and classical juvenoids including fenoxycarb. Their potency in inducing Met-Tai interaction corresponded with the capacity to block metamorphosis in P. apterus larvae and to stimulate oogenesis in reproductively arrested adult females. Molecular modeling demonstrated that the high potency correlates with high affinity. This is a result of malleability of the ligand-binding pocket of P. apterus Met that allows larger peptidic ligands to maximize their contact surface. Our data establish peptidic juvenoids as highly potent and species-selective novel JHR agonists.
Keywords: Peptides; Insecta; rozmnožování; Animals; juvenilní hormony; metamorphosis; Ligands; ligand-binding pocket; Female; hmyz; oogenesis; Methoprene; Larva; Reproduction; ženské pohlaví; zvířata; methopren; larva; Juvenile Hormones; ligandy; peptidy; hormone receptor; juvenile hormone